CHALLENGES AND POLICY SUPPORTS IN INDONESIAN PHARMACEUTICAL RAW MATERIALS INDUSTRY - Erwan Hermawan; Nur Anis Hadiyati; Adiarso Adiarso; Ermawan Darma Setiyadi; Siti Zunuraen; Dudi Hidayat; Anwar Wahyudi; Hartini Ahadiyatur Ru'yi (Universitas Airlangga, 2023)
Background: Indonesian pharmaceutical industry is experiencing many challenges, spesficically their raw materials mostly are imported products. Several factors that cause the pharmaceutical raw materials industry to be challenging are lack of mastery of technology, lack of government support, low budget for R&D, high costs of development and time consuming, and low innovation incentives. Aims: This study aims to conduct a study on the strategies for developing the pharmaceutical raw material industry in Indonesia Methods: This study employed a qualitative method, the data triangulation gathered from interviews and discussions with several industries and institutions. The study was conducted for six months in 2022. Results: The policies that are required to be implemented to make the pharmaceutical raw materials industry thrive are (i) the presence of a clear grand strategy, (ii) determining the priority of pharmaceutical raw materials based on industrial needs, (iii) protecting domestic products, (iv) increasing health spending, (v) strengthening basic chemical product, and (vi) increasing the budget for R&D. Conclusion: Some policies that can be enhanced include providing incentives and policies that favor the local pharmaceutical raw material industry, ranging from regulated prices, putting an end to dependence on imported products, tax incentives, domestic products protection through import tariff policies, energy subsidies, technology transfers, et cetera. Keywords: pharmaceutical raw materials, policy, pharmaceutical